RECOGNIZING POSSIBLE LIMITATIONS OF E-LEARNING THROUGH EDMODO - Farha Alia Mokhtar (Proceedings of The ICECRS, 2016)
When addressing the topic of e-learning integration via Edmodo, two concerns arise. First, isEdmodo vulnerable to internal or external factors which may become barriers to its effective implementation? Second, if Edmodo has limitations to its use, how can it be diminished to ensure optimum teaching learning experiences? This paper investigates contributing factors that limit Edmodo’s application as a learning management system (LMS) for educational purposes. The results suggest possible limitations of Edmodo; lack of face-to-face interaction, facilities that might not be available to all students and distractions that may pose a threat in online learning environments. Propositions to overcome those limitations suggested in this paper are; face to face interaction to be maintained while supplemented with assignments through Edmodo, ensuring facilities are provided or available prior to execution and inculcate intrinsic motivation for students to stay focus when completing tasks online.